Influence of dentine debris and organic tissue on the properties of sodium hypochlorite solutions. (2nd August 2018) - Tejada, S.; Baca, P.; Ferrer‐Luque, C. M.; Ruiz‐Linares, M.; Valderrama, M. J.; Arias‐Moliz, M. T.
Abstract: Aim: To determine the free available chlorine of 2.5% sodium hypochlorite (NaOCl) alone and combined with 9% etidronic acid (HEDP) in the presence of inhibitors, organic tissue and organic tissue plus dentine debris; to evaluate the influence of dentine debris on the tissue‐dissolving capacity of both NaOCl solutions; and to determine the antimicrobial action of these solutions when in contact with organic tissue and organic tissue plus dentine debris. Methodology: The available chlorine of the solutions over time in the absence and presence of the inhibitors was measured using a titration method. The organic tissue dissolution by the solutions alone and in the presence of dentine powder was evaluated by weighing bovine tissue specimens before and after exposure to the solutions for 3 and 10 min. For the antimicrobial activity, biofilms of Enterococcus faecalis were exposed to the solutions for 3 min in the absence and presence of organic tissue and organic tissue + dentine debris. The biovolume and percentage of damaged membrane cells of the biofilm were measured by means of confocal microscopy and the live/dead technique. Nonparametric tests were used to determine statistical differences ( P  <   0.05). Results: Both inhibitors consumed the free available chlorine of the solutions over time. The presence of dentine debris significantly reduced the tissue dissolution capacity of the NaOCl solutions ( P  <   0.05). The percentages of biovolume reduction were not affected by the presence of the inhibitors in the two NaOCl solutions, whereas the percentage of damaged membrane cells was significantly reduced ( P  <   0.001). Overall, a similar behaviour was observed in the NaOCl and NaOCl/HEDP groups. Conclusions: The presence of organic tissue and organic tissue + dentine debris favoured rapid consumption of the free chlorine of NaOCl and NaOCl/HEDP. This resulted in a decreased ability to dissolve organic tissue without affecting the short‐term antimicrobial activity.